Start at the Top: Successfully Integrating Information and Communication Technologies in Schools by Training Principals - IsaBelle, Claire; Lapointe, Claire (Alberta Journal of Educational Research, 2003)
This exploratory study aims to evaluate school principals' perceptions of their ability to assist teachers in the use of information and communication technologies (ICTs) and on factors that facilitate the integration of technology in the classroom. Correlational analyses show that the more principals use ICTs both for technical and instructional purposes, the easier it is for them to support teachers in the integration of technology. Also, the higher their perception is of their ability to assist teachers in the use of ICTs, the more comfortable they feel in supporting them. It would appear, therefore, that ICTs training for school principals, although still uncommon in university programs, constitutes an important prerequisite to the successful integration of ICTs in schools.